2021
DOI: 10.1057/s41254-021-00204-8
|View full text |Cite
|
Sign up to set email alerts
|

Rural place branding from a multi-level perspective: a Danish example

Abstract: Few studies have looked at the interaction of place branding practices of geographically linked places. Moreover, the different administrative contexts of the linked places and the resulting different place branding approaches have not been taken into consideration. This study provides insight on the interactions of the brands and branding initiatives of higher-level administrative rural places and lower-level places within their territory. A qualitative study was conducted based on the cases of three Danish m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Doyle (2019) illustrates this with the case of Medellı ´n and notes that "while outsiders see Medellı ´n as being a 'model', this is generally not received by insiders" (p. 329). Meanwhile, assessing the effectiveness of place branding policy poses a challenge (Gulisova et al, 2021b) because the outcomes of place branding are not always straightforward. Indeed, place branding policy often oversimplifies place branding by reducing it to the tactics of commercial promotional advertisements and slogans.…”
Section: Place Branding and Public Policymentioning
confidence: 99%
See 2 more Smart Citations
“…Doyle (2019) illustrates this with the case of Medellı ´n and notes that "while outsiders see Medellı ´n as being a 'model', this is generally not received by insiders" (p. 329). Meanwhile, assessing the effectiveness of place branding policy poses a challenge (Gulisova et al, 2021b) because the outcomes of place branding are not always straightforward. Indeed, place branding policy often oversimplifies place branding by reducing it to the tactics of commercial promotional advertisements and slogans.…”
Section: Place Branding and Public Policymentioning
confidence: 99%
“…In fact, place branding is fundamentally a matter of governance involving a network of actors, heavily reliant on stakeholder input to address policy challenges (Klijn and Koppenjan, 2016). Many cases, such as those in Denmark (Gulisova et al , 2021b) and Canada (Arku, 2014), have demonstrated the pivotal role of government in facilitating stakeholder collaboration within the place branding process. However, this can also introduce risks, such as insufficient consultation with local communities (Bichler, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The place brand topic is a concept worked out by several authors [1,[8][9][10] and can easily be found in the scientific literature of branding and marketing scientific journals. However, there are many studies that establish different classifications, such as superior place branding and inferior place branding [21], place brand identity [22], and place physics, place practices, and place personality [23]. Almeida [2] studies place branding and territorial brand separately.…”
Section: Place Brand and Territorial Brand Typologies In The Scientif...mentioning
confidence: 99%
“…De Rosa et al , 2019; Foroudi et al , 2016; Larsen, 2018; Rabbiosi, 2016; Truong et al , 2018; Zenker et al , 2017). In contrast to place branding of nations and urban centers, which primarily aims to attract tourists, investors and migrants, branding of rural areas emphasizes the abilities and requirements of the local populace and fosters internal development (Donner et al , 2017; Gulisova et al , 2021). Nonetheless, relatively little scholarly attention has been directed to rural place branding, and only a few notable studies are available (e.g.…”
Section: Introductionmentioning
confidence: 99%